A multi-mode operation control strategy for flexible microgrid based on sliding-mode direct voltage and hierarchical controls. (March 2016) - Zhang, Qinjin; Liu, Yancheng; Zhao, Youtao; Wang, Ning
Abstract: Multi-mode operation and transient stability are two problems that significantly affect flexible microgrid (MG). This paper proposes a multi-mode operation control strategy for flexible MG based on a three-layer hierarchical structure. The proposed structure is composed of autonomous, cooperative, and scheduling controllers. Autonomous controller is utilized to control the performance of the single micro-source inverter. An adaptive sliding-mode direct voltage loop and an improved droop power loop based on virtual negative impedance are presented respectively to enhance the system disturbance-rejection performance and the power sharing accuracy. Cooperative controller, which is composed of secondary voltage/frequency control and phase synchronization control, is designed to eliminate the voltage/frequency deviations produced by the autonomous controller and prepare for grid connection. Scheduling controller manages the power flow between the MG and the grid. The MG with the improved hierarchical control scheme can achieve seamless transitions from islanded to grid-connected mode and have a good transient performance. In addition the presented work can also optimize the power quality issues and improve the load power sharing accuracy between parallel VSIs. Finally, the transient performance and effectiveness of the proposed control scheme are evaluated by theoretical analysis and simulation results. Highlights: Three-layer hierarchical structure for flexible microgrid is adopted. The direct voltage control based on adaptive sliding-mode method is proposed. Virtual negative impedance reduces the power coupling caused by line resistance. Good transient performance between different operation modes is verified. The VSIs can share the load power proportionally to their power ratings.